Odorant binding protein 18 increases the pathogen resistance of the imported willow leaf beetle, Plagiodera versicolora - Rong, Haoling; He, Xin; Liu, Yipeng; Liu, Mei; Liu, Xiaolong; Lu, Min (Frontiers in Cellular and Infection Microbiology, 2024)
Background Insect odorant-binding proteins (OBPs) are a class of small molecular weight soluble proteins. In the past few years, OBPs had been found to work as carriers of ligands and play a crucial role in olfaction and various other physiological processes, like immunity. A subset of insect OBPs had been found to be expressed differently and play a function in immunity of fungal infection. However, there are few studies on the role of OBPs in immunity of bacterial infection. Methods To identify the immune-related OBPs of Plagiodera versicolora after infected by Pseudomonas aeruginosa, we determined the mortality of P. versicolora to P. aeruginosa and selected the time point of 50% mortality of larvae to collect samples for RNA-seq. RNAi technology was used to investigate the function of immune-related OBPs after P. aeruginosa infection. Results RNA-seq data shows that PverOBP18 gene significantly up-regulated by 1.8-fold and further RT-qPCR affirmed its expression. Developmental expression profile showed that the expression of PverOBP18 was highest in the pupae, followed by the female adults, and lower in the 1st-3rd larvae and male adults with lowest in eggs. Tissue expression profiling showed that PverOBP18 was dominantly expressed in the epidermis. RNAi knockdown of PverOBP18 significantly reduced the expression of bacterial recognition receptor gene PGRP and antibacterial peptide gene Attacin and reduced the resistance of P. versicolora to P. aeruginosa infection. Conclusion Our results indicated that PverOBP18 gene increased the pathogen resistance of P. versicolora by cooperating with the immune genes and provided valuable insights into using OBPs as targets to design novel strategies for management of P. versicolora.